Optimization of copper(I) thiocyanate as hole transport material for solar cell by scaps-1D numerical analysis - Arith, Faiz; Aliyaselvam, Omsri Vinasha; Mat junos, Siti Aisah; Izlan, Nurhazwani; Mohd Said, Muzalifah; Mustafa, Ahmad Nizamuddin (Przegląd Elektrotechniczny, 2022)
In SSDSSC, various key parameters of CuSCN as HTM were explored using SCAPS-1D simulation software. A layer thickness of 3 µm with a moderate value of interface defect density was obtained yielding 2.56% of PCE in SSDSSC. TiO2 ETM and Ni back contact was found to be the best combination with CuSCN HTM in SSDSSC. An excellent temperature gradient in a range between -0.04%/K and -0.05%/K was demonstrated, showing that the temperature tolerances of the studied devices are encouraging. In addition, PCE as high as 31.31% has been achieved by substituting the N719 dye with a perovskite absorbent of CH3NH3SnI3, and hence exceeding the previously reported PCE value in PSC. Other parameters that have been optimized are retained. Furthermore, the quantum efficiency of such structure has proved that cells with CH3NH3SnI3 absorbent layer can absorb a wider range of the light spectrum, enhancing the power conversion efficiency.